Підходи до комерціалізації результатів інноваційної діяльності спільних підприємств - Кайкунь, У.; Яструбський, М. Я.; Kaikun, Wu.; Yastrubskyy, M. (Видавництво Львівської політехніки, 2024)
Розглянуто різні підходи щодо комерціалізації результатів інноваційної діяльності спільних підприємств. Унаслідок огляду результатів оцінювання інноваційної діяль- ності країн світу згенеровано схему ранжування країн-лідерів у розрізі напрямів інно- ваційної діяльності. Описано процес комерціалізації результатів інноваційної діяльності підприємств. Систематизовано методи оцінювання потенціалу комерціалізації іннова- ційної діяльності та розглянуто підходи оцінювання її ефективності. Проілюстровано порядок оцінювання рівнів придатності до комерціалізації інноваційної розробки. За ре- зультатами проведених досліджень побудовано загальну схему комерціалізації інно- вацій.

Various approaches to the commercialization of the results of innovative activities of joint enterprises are considered. According to the results of the review of the results of the evaluation of the innovative activity of the countries of the world, a ranking scheme of the leading countries in terms of the directions of innovative activity was generated. The process of commercialization of the results of innovative activities of enterprises is described. Systematized methods of evaluating the potential of commercialization of innovative activity, among which the method of technological audit, the method of fuzzy logic and the four-dimensional approach are highlighted. Approaches to evaluating its effectiveness are considered. Emphasis is placed on the main criteria in approaches to the commercialization of innovations, namely on the evaluation of the potential of commercialization and the assessment of its effectiveness. The list of indicators allowing to evaluate the financial result of the commercialization of the company’s innovations is highlighted. Methods of assessing the prospects and readiness for market commercialization of innovative developments, which are most adaptable for joint ventures, are described. The priority list includes the methodology for assessing the readiness for market commercialization of scientific developments, the TRL (Technology Readiness Level) methodology, developed by the US National Aerospace Agency NASA, and the TPRL (Technology Project Readiness Level) methodology. The main centers of transformation of innovative ideas or research results into marketable products or services are highlighted. The focus is on Technology Transfer Offices (TTO), startup accelerators and incubators, public-private partnerships, direct investment in research and development, open innovation, cluster innovation projects, and market-oriented innovation. The procedure for assessing the levels of suitability for commercialization of innovative development is illustrated. Based on the results of the conducted research, a general scheme for the commercialization of innovations was built.
Approaches to commercialization of the results of innovative activities of joint ventures
Keywords: інноваційна діяльність; комерціалізація інновацій; спільні під- приємства; методика оцінювання інновацій; innovative activity; commercialization of innovations; joint ventures; innovation assessment methodology; 330.341.1; 330.142.2